Reconstruction of the Density Profile for the EAST Tokamak Based on Polarimeter/Interferometer and Microwave Reflectometer Systems*supported by the National Magnetic Confinement Fusion Science Program of China (Nos. 2013GB106003, 2014GB106004 and 2014GB106002) and National Natural Science Foundation of China (Nos. 11475221 and 11105184). (September 2015) - Zhu, Xiang; Zeng, Long; Liu, Haiqing; Jie, Yinxian; Zhang, Shoubiao; Hu, Jiansheng; Gao, Xiang
Abstract A plasma density profile reconstruction procedure based on the Park matrix method has been developed for both circular and elongated plasma configuration on the Experimental Advanced Superconducting Tokamak (EAST). This method incorporates the line integrated electron density measured by the HCN interferometer and polarimeter/interferometer (POINT) system, the equilibrium fit (EFIT) based on magnetic measurements and the edge electron density profile provided by the microwave reflectometer. It is shown that when the magnetic flux surfaces are slightly corrected, the fitting error is less than 5% in comparison with the measurement data.